PENGARUHBULLYINGTERHADAPKEPERCAYAANDIRISISWA KELAS IV DALAM MATA PELAJARAN PJOK DI SD NEGERI 05 TULUNG SELAPAN - Ilpa Rahmadani; Endie Riyoko; Endang Surtiyoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is an effect of Bullying on the self- confidence of grade IV students at SD Negeri 05 Tulung Selapan. The type of research that will be used in this study is an experimental method with the effect of bullying on the self-confidence of grade IV students in the subject of PJOK at SD Negeri 05 Tulung Selapan. The research sample used in this study was grade IV students of SD Negeri Tulung Selapan as an experimental class. Based on the results of the research conducted at SD Negeri 05 Tulung Selapan, it can be concluded that the hypothesis test obtained a t-count value of 3.426, and a t-table value of 1.717. meaning t-count> t-table, then Ha is accepted and Ho is rejected. Therefore, it can be concluded that there is a significant influence of Bullying on students' self-confidence in PJOK learning for class IV.A students of SD Negeri 05 Tulung Selapan